Consensus algorithms blockchain: a comparative study - hattab, Siham; Alyaseen, Imad Fakhri Taha (IIUM Press, International Islamic University Malaysia, 2019)
A blockchain is a Distributed Ledger Technology that has been defined as a “distributed, shared, encrypted database that serves as an irreversible and incorruptible repository of information. Blockchain can be defined as a peer-to-peer distributed ledger that is cryptographically secure, append-only, immutable and updatable only via consensus or agreement among peers. In blockchain platforms, each transaction in the public ledger is verified by consensus of the majority of the system participants in a transparent and secure way. The consensus algorithm refers to the process of attaining an unified agreement on the state of the network in a decentralized way and to facilitate the verification and validation of information being added to the blockchain. This paper aims at providing a comparison between most of the recent consensus algorithms regarding the scalability of the algorithm; the type of blockchain, node identity, the performance of the algorithm (in terms of throughput & latency) and Adversial Tolerance and to deliver a solid basis for discussions about current statistics. In this research, we also presented a new category of the Blockchain consensus algorithms, which consist of three groups as follows; the proof based on Hardware, the proof based on stake, and the proof based on voting.